A loop-mediated isothermal amplification assay for the rapid diagnosis of soybean rust caused by Phakopsora pachyrhizi - Haibing Ouyang; Zhichao Zhang; Guangzheng Sun; Huawei Yang; Wenwu Ye; Yuanchao Wang (Phytopathology Research, 2023)
Abstract Soybean rust caused by the fungus Phakopsora pachyrhizi is one of the most destructive diseases to soybean production worldwide. For the rapid diagnosis and the control of soybean rust, we developed a loop-mediated isothermal amplification (LAMP) assay that targets a P. pachyrhizi-specific gene (Phapa_6409908) identified from a comparative genomic analysis of 61 Pucciniomycotina strains. Using a set of screened primers and the optimized reaction conditions of 62°C for 70 min, the LAMP assay can detect P. pachyrhizi while excluding other plant pathogens. The assay consistently showed high sensitivity in detecting low contents of P. pachyrhizi DNA (10 pg). We confirmed the practical application of this LAMP assay in diagnosing soybean rust using soybean leaf samples collected from fields in four cities of Sichuan Province, China, in 2020 and 2021. The developed LAMP assay provides a specific, sensitive, and rapid method for the diagnosis of soybean rust caused by P. pachyrhizi, which can assist in the prediction, prevention, and control of this major soybean disease.